Job Happiness in Startups: A Study of Job Autonomy, Work-Life Balance, and Social Support - Suparjiman, Suparjiman (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2024)
Working in startups has its own dynamics, as it emphasizes flexibility and freedom for employees to complete their work. This study aims to understand the drivers of job happiness for startup employees by looking into their job autonomy, work-life balance, and social support. To obtain the data, we distributed questionnaires through online platforms to 165 startup employees in Bandung and Jakarta who participated as the respondents of this study. The data is then analyzed using multiple linear regression with SPSS 26 software. The findings indicate that job autonomy, work-life balance, and social support partially and simultaneously lead to the job happiness of startup employees. These results suggest that fostering a supportive and balanced work environment with a high degree of autonomy can significantly enhance employee well-being in startups. Organizations can leverage these insights to create targeted HR strategies that promote happiness and, in turn, improve employee retention and productivity.